Writing mobile lives, 1500-1700 - Holmberg, Eva Johanna (Cambridge elements. Elements in travel writing, 2024)
This Element develops and showcases a new methodological framework in which to study the connections between early modern travel writing and life- and self-writing. Turning the scholarly focus in the study of travel writing from eye-witnessing and proto-ethnography of foreign lands to the 'fashioned' and portrayed selves and 'inner worlds' of travellers - personal memory, autobiographical practices, and lived yet often heavily mediated travel experiences - it opens up perspectives to travel writing in its many modes, that extend both before and after 'lived' travels into their many pre- and afterlives in textual form. This title is also available as Open Access on Cambridge Core.